Utilização de molibdênio via foliar no enriquecimento de sementes de soja - Fonseca, Fernando Cavicchioli (2006)
The use of Mo rich seeds is an alternative for supplying Mo that has presented consistent results on increasing NBF and soybean yield. Soybean enrichment with molybdenum was analyzed through leaf application during the reproduction stage, as potassium molybdate, to optimize its use in soybean culture. The experiment was done on a sandy soil, classified as a neosol, located at the Fazenda Adriana, in the county Alto Garças MT. The experimental design was randomized blocks with 6 treatments and 6 repetitions. The treatments were a control with no MO, a Standard with 800 g ha-1 Mo, using sodium molybdate divided into two applications, in R3 and R5.4; and four treatments using potassium molybdate, with a single application at R5.1, in the doses 91, 182, 273 or 364 g ha-1 Mo. Each experimental unit consisted of nine 7 m long rows spaced 0,45m from each other. The area evaluated measured 7,2 m2, consisting of the four 4 m long rows, excluding the outside rows and 1.5 m at each row end. The cultivar used was FMT-Perdiz. Yield, molybdenum contents and accumulation in the seeds were evaluated. There were no significant differences for yield among the treatments. Molybdenum contents in the seeds increased according to leaf applications of potassium molybdate (y = 1,947667 + 0,040086 x). Both Mo accumulation and contents in the seeds presented significant differences, and the application of 364 g ha-1 Mo, as potassium molybdate (18,23 mg kg-1 and 73,54 g ha-1) were greater than the standarda treatment with 800 g ha-1 Mo as sodium molybdate (13,74 mg kg-1 and 59,40 g ha-1). It can be concluded that Mo leaf application in the reproductive stage, for soybean seed enrichment with molybdenum did not affect the crop yield, and a single application of 364 g ha-1 Mo as potassium molybdate resulted in seeds richer in Mo than two applications of 400 g ha-1 Mo each (800 g ha-1 Mo) as sodium molybdate, and leaf application of potassium molybdate, in soybean reproductive stage was effective in supplying Mo for the plants and to obtain molybdenum rich seeds.